Pengaruh Kinerja Keuangan Leverage dan Ukuran Perusahaan Terhadap Materialitas Pada laporan Keuangan Berkelanjutan - Nasution, M. Afif Herliandi (Politeknik Raflesia Press, 2024)
The Influence of Financial Performance, Leverage, and Firm Size on Materiality in Sustainability Reports Abstract: This study aims to examine the influence of financial performance, leverage, and firm size on the level of materiality in corporate sustainability reports. The methodology employed is regression analysis on panel data of companies listed on the stock exchange. Data were extracted from financial statements and corporate sustainability reports for the period 2020-2022. The results of the analysis indicate that the financial performance of companies has a significant influence on the level of materiality in sustainability reports. Companies tend to be more transparent in disclosing material information when their financial performance is better. However, there is no significant influence from leverage and firm size on materiality. These findings highlight the importance of financial performance in determining the level of materiality in sustainability reports, as well as indicating that other factors such as leverage and firm size may have more limited impacts in this context.